PENGARUH HUBUNGAN INDUSTRIAL TERHADAP KINERJA KARYAWAN DENGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI SEBAGAI VARIABEL PEMODERASI - Roz, Kenny; Widagdo, Bambang (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
This research purpose to examine the influence of industrial relations to employee performance, the role of transformational leadership and compensation under the influence of industrial relations to employee performance, and the CV. In order Sari Jaya Karangploso Malang. This research is explanatory. Samples in this study using saturated sample of 80 respondents employees working on the CV. In order Sari Jaya Karangploso Malang. Results of analysis Partial Least Square (PLS) This study shows that industrial relations positive and significant effect on employee performance, strengthen the influence of transformational leadership style industrial relations to employee performance, and compensation for strengthening the influence of industrial relations to kienerja employees at CV. Agar Sari Jaya Karangploso Malang.